THE ROLE OF ORGANISATIONAL CULTURE IN HIGHER EDUCATION - Julija Mironova; Biruta Sloka; Valentina Djakona (Baltic Journal of Economic Studies, 2025)
Since the late 20th century, organisational culture has attracted considerable attention from researchers worldwide, becoming a key subject of academic inquiry. In the context of higher education, organisational culture has been shown to exert a significant influence on institutional development and workplace dynamics. A comprehensive grasp of this concept empowers university administration to cultivate a professional environment conducive to the success of faculty and staff. The present study explores theoretical perspectives on organisational culture and examines the views of academic staff across various countries regarding key aspects of institutional culture. A particular focus is placed on faculty self-assessments of their perceived appreciation by both university management and students. The research methodology encompasses an analysis of scientific literature and a survey of teaching staff with regard to organisational culture in higher education. The analysis of data involves the utilisation of descriptive statistics, cross-tabulations, hypothesis testing through the implementation of t-tests, analysis of variance (ANOVA), and correlation analysis. The findings provide insights into the core values upheld by higher education institutions from the organisational culture perspective, offering a deeper understanding of faculty experiences and institutional practices.